Orthodontic management of compromised first permanent molars with bilateral posterior crossbite, severe crowding and impacted maxillary canines. (Bangladesh Journal of Medical Science, 2021)
Background: A unique clinical challenge presents when dealing with a compromised first permanent molars with bilateral posterior crossbite, severe crowding and impacted maxillary canines with skeletal class II base malocclusion patient.Case presentation: 14-year-old female patient had dental Class II skeletally, complicated with increase overjet, badly destructed permanent mandibular 1st molars constricted maxillary arch. Extraction of 1st molars followed by expansion have been planned to relieve crowding. Extraction of 1st molars in this time (furcation of 3rd molars start to develop) help in replacement by 2nd molars. In the progression of treatment,Conclusion: A well-balanced and esthetic occlusion by edge wise orthodontic treatment has been archived in this case.Bangladesh Journal of Medical Science Vol.20(4) 2021 p.926-929